A true-1-V 300-μW CMOS-subthreshold log-domain hearing-aid-on-chip. - Serra-Graells, F. (IEEE Journal of solid state circuits)
This paper presents a true very low-voltage low-power complete analog hearing-aid system-on-chip as a demonstrator of novel analog CMOS circuit techniques based on log companding processing and using MOS transistors operating in subthreshold. Low-voltage circuit implementations are given for all of the required functions including amplification and automatic gain control filtering, generation, and pulse-duration modulation. Based on these blocks, a single 1-V 300-μA application specific integrated circuit integrating a complete hearing aid in a standard 1.2-μm CMOS technology is presented along with exhaustive experimental data. To the authors' knowledge, the presented system is the only CMOS hearing aid with true internal operation at the battery supply voltage and with one of the lowest current consumptions reported in literature. The resulting low-voltage CMOS circuit techniques may also be applied to the design of A/D converters for digital hearing aids.